Functional indicators of the female athlete`s body specializing in rowing - Bogush, V.; Getmantsev, S.; Bogatyirev, K.; Reznichenko, O.; Kosenchuk, V.; Verteleckiy, O.; Kulakov, Y. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to conduct a comprehensive study of the functional state of female athlete`s specializing in rowing, for the subsequent determination of the prospects in this sport.